The Role of the Local Government in Monitoring and Maintenance Bridges, Learning from the Case of the Collapsed Bridge in Nusa Lembongan Bali - Nyoman Diah Utari Dewi1; V. Rudy Handoko (Indonesian Association for Public Administration (IAPA), 2019)
There are many issues of infastructure especially in the remote area in the islands of Indonesias and goes viral about collapsed bridges and how students and teachers transported to their school by crossing the collapsed bridges where is the only way to go to their school in the cross of their village. Although the government authority and Standard Operation Procedure are in ruled and structured but still collapsed bridges happened in Indonesia. The main objective of this study is to analyze why the monitoring are failed, learning from the case of the collapsed bridge happened in Nusa Lembongan island in Bali. This study employed the qualitative descriptive methodology. The data collection techniques used were literature study, observation, and interviews with the goverrnment authority in PUPR Department and Klungkung Municipality and stakeholders in Nusa Lembongan Island. The study results shows that due to unclear division between central and local government role and budget, the division of monitoring and maintenance of bridge infrastructure has become unclear resulting in an accident. The unclear owner of the assets of the bridge caused the maintenance of the bridge to be displaced. The cased of collapsed bridge in Nusa Lembongan happened because of the unclear distribution of authority in the monitoring and maintenance between the Bali Provincial and Klungkung Municipaity Government.